Analysis of Polymorphisms in Interleukin-10, Interleukin-6, and Interleukin-1 Receptor Antagonist in Mexican-Mestizo Women with Pre-eclampsia - Valencia Villalvazo, Elith Yazmin (Mary Ann Liebert, Inc., 2012)
Due to the fact that studies seeking associations of polymorphisms in regulatory regions of cytokine genes with pre-eclampsia (PE) have not always been consistent in different population analyses, the aim of this study was to investigate the possible association between rs1800896 of interleukin-10 (IL-10), rs1800795 of interleukin-6 (IL-6), and the variable number of tandem repeats (VNTR) in intron 2 of interleukin-1 receptor antagonist (IL-1Ra), as well as gene–gene interactions between these three polymorphisms with the presence of PE in Mexican-Mestizo women and one Amerindian population from México (Maya). A case–control study was performed where 411 pre-eclamptic cases and 613 controls were genotyped. For the rs1800896 of IL-10 and rs1800795 of IL-6, we used real-time polymerase chain reaction (PCR) allelic discrimination and for the VNTR of IL-1Ra, PCR. Allele frequency differences were assessed by Chi-squared test; logistic regression was used to test for associations; a gene–gene interaction was conducted. Genotypic and allelic distribution of the polymorphisms was similar in our population. The estimated of the gene–gene interaction between the polymorphisms did not differ significantly. However, we observed important differences in the distribution of the alleles and genotypes of the three polymorphisms analyzed between Mestiza-Mexicanas and Maya-Mestizo women. In conclusion, we did not find an association between polymorphisms in IL-10, IL-6, and IL-1Ra and PE in Mexican-Mestizo and Maya-Mestizo women. To our knowledge, this is the first time that these three polymorphisms were analyzed together with gene–gene interaction in women with PE.